Biotherapeutic potentials of diverse probiotics of the Himalayan region: A Review - Nikita Bahuguna; Jigisha Anand; Divya Venugopal; Ankit Khanduri; Nishant Rai (Environment Conservation Journal)
The highest ecosystems on Earth are located in India's Himalayan region, covering a distance of 3500 km from Jammu and Kashmir to Arunachal Pradesh in the northeastern part of the country. Limited information on the probiotic diversity within the traditional diets of the Western Himalaya is available. Despite living in the challenging environment of high altitudes, the inhabitants of these areas display healthy and long lifespans, which are primarily attributed to their diet, particularly the traditional fermented foods. The potential for isolating native probiotic bacteria from traditional foods is, therefore, enormous. One of the main strategies for preventative treatment in humans may be to supplement the diet with nutrients that can shield against immune system problems and lower the risk of contracting illnesses like mycosis. The emergence of functional foods and nutraceuticals underscores the importance of reducing reliance on medications and increasing regular consumption of fermented foods. Researchers primarily suggest probiotics and lactic acid bacteria (LAB) as nutraceuticals due to their non-harmful effects on human health, their ability to activate the immune system, and their ability to enhance resistance to various illness situations. As per WHO, probiotic bacteria are defined as “live microorganisms that, when administered in adequate amounts, confer a health benefit on the host.” Antifungal agents like azoles and amphotericin B are recommended as therapeutic agents as per the case. However, the emergence of drug-resistant strains worldwide has reduced the efficacy of these treatments. According to health organizations (national and international, including WHO), there is an urgent need to explore novel and alternative options, including probiotics. The current review highlights the biotherapeutic perspective of diverse probiotic strains, including next-generation probiotics against mycosis.